2023
DOI: 10.3390/ijms241311006
|View full text |Cite
|
Sign up to set email alerts
|

Genome-Wide Identification and Expression Analysis of Auxin Response Factor Gene Family in Linum usitatissimum

Abstract: Auxin response factors (ARFs) are critical components of the auxin signaling pathway, and are involved in diverse plant biological processes. However, ARF genes have not been investigated in flax (Linum usitatissimum L.), an important oilseed and fiber crop. In this study, we comprehensively analyzed the ARF gene family and identified 33 LuARF genes unevenly distributed on the 13 chromosomes of Longya-10, an oil-use flax variety. Detailed analysis revealed wide variation among the ARF family members and predic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 74 publications
0
2
0
Order By: Relevance
“…Duplication events, including tandem duplication and segmental/whole duplication, are the major forces for gene family expansion and functional differentiation during evolution. Previous studies have reported that plant ARF genes expand by undergoing tandem duplication and segmental/whole duplication ( Chen et al., 2023 ; Qi et al., 2023 ). For example, four LuARF genes (two gene pairs) underwent tandem duplication events, whereas 27 (81.8%, 18 gene pairs) underwent segmental/whole duplication events in flax ( Qi et al., 2023 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Duplication events, including tandem duplication and segmental/whole duplication, are the major forces for gene family expansion and functional differentiation during evolution. Previous studies have reported that plant ARF genes expand by undergoing tandem duplication and segmental/whole duplication ( Chen et al., 2023 ; Qi et al., 2023 ). For example, four LuARF genes (two gene pairs) underwent tandem duplication events, whereas 27 (81.8%, 18 gene pairs) underwent segmental/whole duplication events in flax ( Qi et al., 2023 ).…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have reported that plant ARF genes expand by undergoing tandem duplication and segmental/whole duplication ( Chen et al., 2023 ; Qi et al., 2023 ). For example, four LuARF genes (two gene pairs) underwent tandem duplication events, whereas 27 (81.8%, 18 gene pairs) underwent segmental/whole duplication events in flax ( Qi et al., 2023 ). In alfalfa, 14 segmental duplications and two sets of tandem repeats were identified ( Chen et al., 2023 ).…”
Section: Discussionmentioning
confidence: 99%